Mapping the Tax Planning Incentives Behind Royalty Flows: A Qualitative Synthesis of Network Analysis, Gravity Models, and Multinational Profit Shifting Strategies - Yessica Amelia; Muhammad Rizal (International Journal of Management, Accounting & Finance (KBIJMAF), 2026)
This qualitative literature review examines how tax planning incentives shape international royalty flows by synthesizing insights from network analysis, gravity models, and the literature on multinational profit shifting. The review highlights that royalty payments are not solely driven by economic fundamentals such as market size, innovation intensity, or bilateral trade costs, but are systematically influenced by corporate income tax differentials, withholding taxes, and the structure of international tax treaty networks. Network-based approaches reveal the central role of conduit jurisdictions and treaty shopping routes in facilitating the redirection of royalty flows, while gravity models provide counterfactual benchmarks to identify deviations attributable to tax-motivated behavior. The synthesis further shows that profit shifting via intellectual property relocation, although smaller in scale than other channels, generates non-trivial revenue losses and remains structurally embedded in the international tax system. Overall, the study underscores the value of integrating network and gravity frameworks to better understand royalty-based tax planning and its policy implications